2019
DOI: 10.1590/s0100-83582019370100125
|View full text |Cite
|
Sign up to set email alerts
|

Physical Compatibility and Stability of Pesticide Mixtures at Different Spray Volumes

Abstract: Available information on physical compatibility and stability of pesticide mixtures is scarce and often divergent. This knowledge is of fundamental importance in the success of pest, disease, and weed control programs. Compatibility and stability of two glyphosate formulations (WG and SL) in a mixture with fluazinam + deltamethrin + trifloxystrobin/cyproconazole at four diluted water concentrations and different times were evaluated under laboratory conditions. The evaluations were performed at the following t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Tank mixtures among herbicides Clincher ® + Ricer ® , Clincher ® + Kifix ® , Clincher ® + Imazethapyr Plus Nortox ® , Clincher ® + Ricer ® + Kifix ® , Clincher ® + Ricer ® + Sirius ® 250 CS, Imazethapyr Plus Nortox ® + Basagran ® 600, between herbicides and insecticides Clincher ® + Ricer ® + Arrivo ® 200 EC, Clincher ® + Kifix ® + Arrivo ® 200 EC, Clincher ® + Imazethapyr Plus Nortox ® + Arrivo ® 200 EC, Clincher ® + Ricer ® + Kifix ® + Arrivo ® 200 EC, Clincher ® + Ricer ® + Sirius ® 250 CS + Arrivo ® 200 EC, Imazethapyr Plus Nortox ® + Basagran ® 600 + Arrivo ® 200 EC, among fungicides Alterne ® + Bim ® 750 BR + Priori ® 250 CS, and between fungicides and insecticides Bim ® 750 BR + Actara ® 250 WG, Alterne ® + Bim ® 750 BR + Priori ® 250 CS + Actara ® 250 WG, and Alterne ® + Bim ® 750 BR + Priori ® 250 CS + Talisman ® did not present any physicochemical change in the spray mix and are therefore compatible to be used in mixtures in the spray tank in plant treatments in rice crops. Moraes et al (2019) found compatibility between the Deltamethrinae + Ghyphosate insecticide interaction in spray solution with consistent physicochemical parameters even after 24 hours of rest.…”
Section: Discussionmentioning
confidence: 66%
“…Tank mixtures among herbicides Clincher ® + Ricer ® , Clincher ® + Kifix ® , Clincher ® + Imazethapyr Plus Nortox ® , Clincher ® + Ricer ® + Kifix ® , Clincher ® + Ricer ® + Sirius ® 250 CS, Imazethapyr Plus Nortox ® + Basagran ® 600, between herbicides and insecticides Clincher ® + Ricer ® + Arrivo ® 200 EC, Clincher ® + Kifix ® + Arrivo ® 200 EC, Clincher ® + Imazethapyr Plus Nortox ® + Arrivo ® 200 EC, Clincher ® + Ricer ® + Kifix ® + Arrivo ® 200 EC, Clincher ® + Ricer ® + Sirius ® 250 CS + Arrivo ® 200 EC, Imazethapyr Plus Nortox ® + Basagran ® 600 + Arrivo ® 200 EC, among fungicides Alterne ® + Bim ® 750 BR + Priori ® 250 CS, and between fungicides and insecticides Bim ® 750 BR + Actara ® 250 WG, Alterne ® + Bim ® 750 BR + Priori ® 250 CS + Actara ® 250 WG, and Alterne ® + Bim ® 750 BR + Priori ® 250 CS + Talisman ® did not present any physicochemical change in the spray mix and are therefore compatible to be used in mixtures in the spray tank in plant treatments in rice crops. Moraes et al (2019) found compatibility between the Deltamethrinae + Ghyphosate insecticide interaction in spray solution with consistent physicochemical parameters even after 24 hours of rest.…”
Section: Discussionmentioning
confidence: 66%
“…However, its importance and applicability are notorious, as it is a strategy with a high operational yield and high efficiency (Antolin et al, 2021). In this sense, landing spraying is one of the most commonly used forms of applying pesticides (Moraes et al, 2019). In most cases, much attention is paid to the product to be used in the application, neglecting the spraying technique (Contiero et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they are also essential for resistance management programs. However, inappropriate chemical control can cause irreversible environmental and economic impact (Moraes et al, 2019), e.g. change the efficacy or biological activity (synergism and antagonism, phytotoxicity or persistence).…”
Section: Introductionmentioning
confidence: 99%